2013
DOI: 10.1111/bjhp.12043
|View full text |Cite
|
Sign up to set email alerts
|

Thinking positively about chronic illness: An exploration of optimism, illness perceptions and well‐being in patients with Parkinson's disease

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Holding positive beliefs about illness and having an optimistic outlook has been associated with increased well-being across a range of health conditions. However research has indicated that being very optimistic may not actually be beneficial and holding a realistic attitude is more adaptive in some forms of chronic illness, e.g. Parkinson's disease (PD). The present study aimed to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
(54 reference statements)
4
45
1
3
Order By: Relevance
“…Indeed, while avoidance may be seen as a means to retain control during the early phase of psychological adjustment to the disease, most HCPs believed that giving patients the chance to discuss assessments and being directly responsible for nutritional actions early on had the potential to be a more empowering alternative approach to coping and control. At a more general level, this also resonates with a large body of evidence on the influence of perceived control and illness perceptions in people with neurological and neurodegenerative disorders, including Huntington's disease (Arran, Craufurd, & Simpson, 2014;Zarotti, Simpson, & Fletcher, 2017), Parkinson's disease (Hurt et al, 2014;Simpson, Chatzidamianos, Fletcher, Perpetuo, & Eccles, 2018), Alzheimer's disease and mild cognitive impairment (Matchwick, Domone, Leroi, & Simpson, 2014;McIlvane, Popa, Robinson, Houseweart, & Haley, 2008), and MND (Ando et al, 2015;Eccles & Simpson, 2011;. This observation is in line with current theorizations around the psychological adaptation to chronic illness.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, while avoidance may be seen as a means to retain control during the early phase of psychological adjustment to the disease, most HCPs believed that giving patients the chance to discuss assessments and being directly responsible for nutritional actions early on had the potential to be a more empowering alternative approach to coping and control. At a more general level, this also resonates with a large body of evidence on the influence of perceived control and illness perceptions in people with neurological and neurodegenerative disorders, including Huntington's disease (Arran, Craufurd, & Simpson, 2014;Zarotti, Simpson, & Fletcher, 2017), Parkinson's disease (Hurt et al, 2014;Simpson, Chatzidamianos, Fletcher, Perpetuo, & Eccles, 2018), Alzheimer's disease and mild cognitive impairment (Matchwick, Domone, Leroi, & Simpson, 2014;McIlvane, Popa, Robinson, Houseweart, & Haley, 2008), and MND (Ando et al, 2015;Eccles & Simpson, 2011;. This observation is in line with current theorizations around the psychological adaptation to chronic illness.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, participants who took part in the computer-based programme stated that it helped them to keep trying and not give up that easily, which is a crucial aspect with respect to their health status. Previous research studies have shown that a persistent and positive attitude in people with chronic illness was associated with better well-being (Hurt et al, 2013;de Ridder, Schreurs & Bensing, 2000).…”
Section: Positive Impact On Quality Of Lifementioning
confidence: 97%
“…In the short term, there is also evidence that unrealistically positive beliefs may be helpful in facilitating coping and adjustment. 26,27 However, where new information is not integrated into the individual's belief system over the course of the recovery journey, unhelpful or unrealistic beliefs may arise that create difficulties with the adjustment process. Chan et al 4 concluded that at least during the acute stages of recovery, patients' illness beliefs do not appear to be related to the severity of their injury.…”
Section: Within the Clinical Health Psychology Literature Leventhal'mentioning
confidence: 99%